Nutritional intakes, lipid profile and serum apo-lipoproteins concentrations and their relationship with antithyroid, antigliadin and anti-tissue transglutaminase antibodies in patients with Hashimoto’s thyroiditis - Hadizadeh Riseh, Shaghayegh; Mobasseri, Majid; Jafarabadi, Mohammad-Asghari; Abbasalizad Farhangi, Mahdieh; Ajorlou, Elham (Progress in Nutrition, 2016)
Background and aim: Hashimoto’s thyroiditis (HT) is the most common autoimmune thyroid disease and it is in coexistence with many autoimmune disorders, especially celiac disease. The present study is the first to evaluate nutritional intakes in Hashimoto’s thyroiditis patients and the relationship between nutritional intakes and metabolic factors with anti-thyroid, anti-gliadin and anti-tissue transglutaminase antibodies in patients with Hashimoto’s thyroiditis. Methods: This study was performed on 82 women aged 20-50 years including 40 patients with Hashimoto’s thyroiditis and 42 healthy age-matched individuals. Dietary intakes were assessed using a semi- quantitative food-frequency questionnaire (FFQ). Physical activity was obtained by metabolic equivalent (MET) questionnaire. Anthropometric assessments were performed and biochemical assays including thyroid hormones, antithyroid antibodies, anti-tissue transglutaminase and anti-gliadin antibodies, lipid profile and apo-lipoprotein were measured. Results: Serum lipids and apo-liporotein concentrations were higher in patients with Hashimoto’s thyroiditis compared with healthy control group. Moreover these patients had a significantly lower consumption of antioxidants including vitamin E or selenium compared with healthy individuals (P < 0.05). Nutritional intakes and metabolic factor also positively associated with anti-tissue transglutaminase and anti-gliadin antibodies in patients with Hashimoto’s thyroiditis (P < 0.05). Conclusion: Patients with Hashimoto’s thyroiditis had higher metabolic abnormalities and lower intakes of antioxidant including vitamin E and selenium. Moreover significant positive relations were also identified between nutritional parameters and metabolic factors with anti-thyroid, anti-gliadin or anti-tissue transglutaminase antibodies in these patients. Further researches are needed to better clarify these relationships and underlying mechanisms.